Produktivitas Kreatif Tim Penata Kostum dalam Tekanan Waktu pada Program Variety Show Televisi - Arum Githa Putri; Deny Willy Junaidy (Institut Seni Indonesia Yogyakarta, 2022)
Time pressure is unavoidable. This is also experienced by designers who work in the television industry who work with a faster pace. The costume stylist team as the designers whose fulfill the costume needs must also adjust to the conditions they have. The purpose of this research is to identify the factors that influence the costume stylist team in the costume arrangement process and the process they do in developing their ideas in the midst of their limitations. The data collection process in this study was carried out by concurrent experimentation with the protocol by recording and observing directly the creative process of costume styling on two teams of costume stylists, the recorded data was described and given a code classification based on the F-B-S onthology and processing through linkography. Through linkography obtained output data in the form of graphs of entropy, data distribution, and also the distribution process so that it can identify the influencing factors and the design process that is carried out. In this study it was found that (1) the expectations of the costume stylist team for what they wanted to serve and the available commodities were the most influential factors in developing ideas under time pressure during the costume arrangement process. (2) The costume arrangement process is carried out to deal with the time pressure they are doing, by adjusting the ideas developed, reprocessing the available costumes into new costumes, and reviewing ideas with similar experiences.